The Traditions of Children’s Social Sex Education in the Ukrainian Peasant Folklore of the XIX – Beginning of the XX Century (Gender Analysis of the Original Texts) - Prykhod’ko, Hanna (Pedagogical Discourse, 2013)
The article deals with the gender critical analysis of the educational motifs in Ukrainian peasant folklore (songs, sayings, nursery tales, etc.) of the XIX – beginning of the XX century. The special attention is paid to the fact that folklore texts contained the gender problem (social sex). The author describes the influence of the folklore texts on the forming of relations between men and women in Ukrainian peasant society in general and in peasant families in the particular. According to the text the folklore always was an essential educational means, which also was used in the process of children education in its social sex context. In conclusion the author stresses that Ukrainian peasant folklore can be used by scientists as a source research of pedagogy history.